" PROS AND CONS OF TEACHING LISTENING SKILLS FOR DISABLED LEARNERS" (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2022)
In the following article the merits of teaching listening skills for disabled learners will be discussed in detail, providing useful materials and approaches in order to teach English efficiently.